Implementasi Metode Berbasis Masalah pada Pelajaran Aqidah Akhlaq Melalui Kitab Aqidatul Awam dalam Meningkatkan Hasil Belajar Siswa di MI NU Miftahul Ulum Surabaya - Ismail, Moh.; Ali, Moh.; Dodi; Khotimah, Khusnul; Suwistiyonengsih; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
There are many researchers' concerns and concerns about the decline in morals and character that has begun to spread among students, both from elementary schools and beyond, as well as public anxiety about the behavior of the nation's generation which increasingly does not show good morals or character, so that apart from the family environment educational institutions are the beginning of character formation and prevention of moral decline in these generations. MINU Miftahul Ulum Surabaya has a good vision and mission as well as management with several religious activities that other schools don't have, giving rise to the following problem formulation: First, what is the process of implementing problem-based methods in aqeedah akhlaq lessons through the book of aqidatul lay in improving student learning outcomes at MINU Miftahul Ulum Surabaya? ? Third, what are the supporting and inhibiting factors for the implementation of problem-based methods in aqidah akhlaq lessons through the lay book of aqidatul in improving student learning outcomes at MINU Miftahul Ulum Surabaya? The research method used in this study uses qualitative methods with a phenomenological approach. While the results of the research that became the author's findings in the field as well as answers to the problem formulation were asked: First, knowing the process of implementing problem-based methods in aqidah akhlaq lessons through the book of aqidatul lay in improving student learning outcomes at MINU Miftahul Ulum Surabaya. Second, knowing the implications of problem-based methods on aqeedah akhlaq lessons through the book of aqidatul lay in improving student learning outcomes at MINU Miftahul Ulum Surabaya. Third, knowing the supporting factors and inhibiting the implementation of problem-based methods in aqidah akhlaq lessons through the book of aqidatul lay in improving student learning outcomes at MINU Miftahul Ulum Surabaya.